1986. Rapid Identification and Antimicrobial Susceptibility Testing Utilizing the Accelerate Pheno™ System for Gram-Negative Bloodstream Infections and Its Potential Clinical Impact. (26th November 2018) - Schneider, Jack; Wood, James; Schmitt, Bryan; Emery, Christopher; Davis, Thomas; Blevins, Sarah; Hiles, Jon; Desai, Armisha; Wrin, Justin; Manaloor, John
Abstract: Background: This study's aim was to compare pathogen identification (ID) and antimicrobial susceptibility testing (AST) result turnaround times of the Accelerate Pheno™ system (AXDX) against current standard methods (SOC). Secondarily, we assessed whether its implementation for positive blood cultures (PBC) with monomicrobial Gram-negative bacilli could provide theoretical improvement in time to active and optimal antibiotic therapy. Methods: Over 3 months, Gram-negative PBC from 114 patients, including 29 pediatric patients, were identified for the study. Blood cultures were tested on both the Verigene® and AXDX platforms in tandem after flagging positive on the BACTEC® FX system. Isolates were tested on the Bruker MALDI Biotyper® system for ID and VITEK® 2 system (GN73 cards) for AST. Patient charts were then retrospectively evaluated to calculate time to active and optimal therapy. On comparing time to results (ID and AST) for AXDX with SOC, timing calculations to mimic setup and reporting times for tests and results were included. Results: From time of blood culture positivity, mean time to ID averaged 36.3 hours for MALDI-TOF MS, 4.5 hours for the Verigene ® system and 3.6 hours for AXDX, while the mean time to AST averaged 35.8 hours for the VITEK ® 2 system and 8.9 hours for AXDX. Thirty-nine percent (45/114) of patients were not on active therapy at time of positive blood culture. Of these, 29 were put on active therapy within a mean of 21 hours (range: 9.3 hours to 5.6 days), such that 25% of patients could have been put on active therapy sooner had AXDX AST results been available clinically for action by a physician or stewardship team. Similarly, 34 were put on optimal therapy within a mean of 1.3 days (range: 9.3 hours to 5.6 days). Thus, 30% of patients could have had therapy optimized earlier had AXDX AST results been available. Conclusion: Overall, the Accelerate Pheno™ system is a reliable new diagnostic modality that has the potential to significantly reduce time to PBC ID and AST results, as well as time to active and optimal therapy, thus aiding in effective antimicrobial stewardship. Prospective studies evaluating the clinical impact of AXDX on patient outcomes are needed and planned. Disclosures: J. Schneider, Accelerate Diagnostics: Investigator, kits and data management and Research support.